A intertextualidade nas seções de leitura de livros didáticos - Morais, Adriana Negreiros de Almeida (2018)
Reading, under a socio-cognitive-interactional conception of language, requires readers to have recourse to previously acquired knowledge to be, in fact, processed. Given the importance of this process, the textbooks represent a very important support regarding the status of intertextuality, which constitutes an important mechanism for the construction of the meanings of texts. This research aims to analyze the intertextuality present in the activities of the reading sections of the Portuguese Language High School textbooks, considering the approach that is present in these books. For this, we follow the theoretical perspective of Textual Linguistics, which discusses the presuppositions of intertextuality, a relevant factor for the comprehension and production of the most diverse discursive genres. In this context, the general data that compose this research were analyzed in the light of the theoretical conceptions of Piègay-Gros (1996), Bazerman (2006), Koch; Bentes and Cavalcante (2008), Koch and Elias (2014), Cavalcante (2011), Kleiman (1999) on the concept and typifications of intertextuality. We are also guided by the guidelines of the PCN (1998), for the analysis of the corpus, which is composed of three collections of Portuguese language textbooks, selected in the Manual of the National Textbook Program (MNTP). Each collection is composed of three books, one for each series that composes high school. In these books we highlight and analyze 30 activities of linguistic analysis that deal with intertextuality in the reading sections. For the analysis of activities, we use the categories of analysis presented by Piègay-Gros (2010), allusion, reference and citation, whose typologies address the way in which the intertextuality can manifest, by co-presence, similar marks to the approach pointed out by Genette (2010), with whom we identify. We find, through the analysis, that there are didactic manuals that approach the phenomenon, from a perspective that is predominantly linked to the teaching of reading and not grammar, as I thought, that is, text interpretation activities taken from the reading sections are composed of questions whose objective is to problematize the text read, helping the students to take it back and look for aspects that are primordial to their comprehension. Thus, the work with intertextuality from the activities taken from textbooks proves the need for students to work with reading in an integrated way to the different sources of knowledge, going beyond the limits imposed by the text.